Bank Stability Index for Selected Countries with Dual Banking Systems - Karim, Norzitah Abdul; Muhamat, Amirul Afiff; Jaafar, Mohamad Nizam (Journal of Reviews on Global Economics, 2019)
A robust and comprehensive measure of bank stability is crucial to identify healthy banks and save troubled banks from deteriorating in order to avoid banking crises, hence prevented a systemic effect on the overall financial system of the country. The study aims to develop a comprehensive measure of bank stability for selected Organization of Islamic Cooperation (OIC) countries with dual banking systems. The measure is in the form of a composite index, comprehensively adopts relevant indicators from the existing literatures based on annual data from 1999 to 2015, obtained from the Bankscope database. The factor analysis method used by the Organization of Economic Co-operation and Development (OECD) is adopted to develop the index. The findings reveal the comprehensive measure of bank stability for all bank models. The policy implication for the regulatory is to use similar measure of bank stability in monitoring and reporting the stability of different bank models.